2023
DOI: 10.3390/ijerph20043541
|View full text |Cite
|
Sign up to set email alerts
|

Motor Imagery Training Is Beneficial for Motor Memory of Upper and Lower Limb Tasks in Very Old Adults

Abstract: Human aging is associated with a decline in the capacity to memorize recently acquired motor skills. Motor imagery training is a beneficial method to compensate for this deterioration in old adults. It is not yet known whether these beneficial effects are maintained in very old adults (>80 years), who are more affected by the degeneration processes. The aim of this study was to evaluate the effectiveness of a mental training session of motor imagery on the memorization of new motor skills acquired through p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Motor imagery restores damaged motor conduction pathways and stimulates motor cortex networks. There is compelling evidence [78][79][80] that motor imagery and motor execution share the same neural networks related to motor functions. As direct monitoring of motor imagery is challenging, researchers have enhanced the efficacy of motor imagery training by furnishing subjects with real-time feedback on the targeted cortical activity.…”
Section: Nirs As a Therapeutic Tool Imagine Feedbackmentioning
confidence: 99%
“…Motor imagery restores damaged motor conduction pathways and stimulates motor cortex networks. There is compelling evidence [78][79][80] that motor imagery and motor execution share the same neural networks related to motor functions. As direct monitoring of motor imagery is challenging, researchers have enhanced the efficacy of motor imagery training by furnishing subjects with real-time feedback on the targeted cortical activity.…”
Section: Nirs As a Therapeutic Tool Imagine Feedbackmentioning
confidence: 99%
“…Patients can improve their motor performance by repeatedly imagining and simulating the specified actions (Wang et al, 2019 ). These studies observed that motor imagery, as a complementary technique, improved upper limbs motor function (Nam et al, 2019 ; Vourvopoulos et al, 2019 ; Barclay et al, 2020 ; Gaughan and Boe, 2021 ; Hilt et al, 2023 ). However, there is no consensus regarding the intervention protocol for the application of motor imagery.…”
Section: Introductionmentioning
confidence: 99%